2017
DOI: 10.1177/1203475417708163
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Neurofibromatosis Type 1 in Children: A Single-Institution Experience

Abstract: MNF is an underrecognised condition with potential implications for patients. Children mostly present with pigmentary anomalies only. Most patients do not develop associated findings or complications before adulthood, but long-term follow-up will help determine outcomes and possible associations. Recognition and confirmation of the diagnosis is important to provide follow-up and genetic counselling to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…20 Recently, a study of 60 children led by Lara-Corrales and colleagues further characterized mosaic neurofibromatosis, with 65% of mosaic neurofibromatosis children presenting with localized pigmentary changes only and 16.7% presenting with plexiform neurofibromas. 23 Compared with the characteristics described in the literature of pediatric patients with mosaic neurofibromatosis, our data carry a number of notable similarities and differences. Our study agrees with the literature in that children with mosaic neurofibromatosis most commonly present with pigmentary abnormalities.…”
Section: Discussionmentioning
confidence: 55%
“…20 Recently, a study of 60 children led by Lara-Corrales and colleagues further characterized mosaic neurofibromatosis, with 65% of mosaic neurofibromatosis children presenting with localized pigmentary changes only and 16.7% presenting with plexiform neurofibromas. 23 Compared with the characteristics described in the literature of pediatric patients with mosaic neurofibromatosis, our data carry a number of notable similarities and differences. Our study agrees with the literature in that children with mosaic neurofibromatosis most commonly present with pigmentary abnormalities.…”
Section: Discussionmentioning
confidence: 55%
“…2 Individuals with MNF1 may have gonadal mosaicism and offsprings with complete NF1. 9 In the individual case reports of a systematic review on MNF1, majority of cases had neurofibromas only. Also, the cases that presented at the oldest age was the group with neurofibromas only.…”
Section: Discussionmentioning
confidence: 99%
“…However, these criteria do not apply well to the MNF1 cohort as several patients had manifestations on several areas of the body sometimes crossing the midline. Lara-Corrales et al suggested that the ideal way to con rm the diagnosis of MNF1 is a positive NF1 analysis on DNA from affected tissue together with a negative NF1 analysis on DNA from blood (21). However, one of the patients from our MNF1 cohort had a positive NF1 analysis on DNA from both affected tissue and blood, though in a mosaic state and two patients had a negative NF1 analysis on DNA from a plexiform neuro broma and from a CAL spot, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another case had a daughter with generalized NF1 and two unaffected children consistent with gonadal mosaicism (24). (21,22). In 11 cases a pathogenic NF1 variant was detected; an intragenic variant in nine cases and a microdeletion in two cases (21,22).…”
Section: Clinical Featuresmentioning
confidence: 98%
See 1 more Smart Citation